2019
DOI: 10.1101/551390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SURF1 mutations causative of Leigh syndrome impair human neurogenesis

Abstract: Mutations in the mitochondrial complex IV assembly factor SURF1 represent a major cause of Leigh syndrome (LS), a rare fatal neurological disorder. SURF1-deficient animals have failed to recapitulate the neuronal pathology of human LS, hindering our understanding of the disease mechanisms. We generated induced pluripotent stem cells from LS patients carrying homozygous SURF1 mutations (SURF1 iPS) and performed biallelic correction via CRISPR/Cas9. In contrast to corrected cells, SURF1 iPS showed impaired neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Similarly, mitochondrial dysfunction likely starts before birth in SURF1-associated Leigh syndrome. Shreds of evidence suggest that SURF1 mutations lead to metabolic impairments in neural progenitor cells (NPCs), which cannot switch from glycolytic to OXPHOS metabolism, with subsequent aberrant proliferation and insufficient support for neuronal morphogenesis [ 416 ]. A similar neuronal impairment was reported in a SURF1 ko pig model [ 417 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mitochondrial dysfunction likely starts before birth in SURF1-associated Leigh syndrome. Shreds of evidence suggest that SURF1 mutations lead to metabolic impairments in neural progenitor cells (NPCs), which cannot switch from glycolytic to OXPHOS metabolism, with subsequent aberrant proliferation and insufficient support for neuronal morphogenesis [ 416 ]. A similar neuronal impairment was reported in a SURF1 ko pig model [ 417 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…NSCs require a metabolic shift towards oxidative phosphorylation during the process of neuronal differentiation [ 421 ]. Therefore, OXPHOS defects may inhibit this shift impairing neuronal differentiation and driving neural stem cells (NSCs) to a proliferative and less differentiated state [ 416 ]. We recently tested inductors of oxidative metabolism (developed and patented by Professional Dietetics, IT) composed of TCA cycle intermediates, specific amino acids, and co-factors that helped enhance mitochondrial function in different in vitro and in vivo models.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Previous studies using cells from LS patients carrying homozygous SURF1 (c.769G>A and c.530T>G) (Inak et al, 2019) and MT-ATP6 (m.9185T>C) (Lorenz et al, 2017) mutations showed an abnormal generation of neural lineages in vitro using two-dimensional culture systems. SURF1 mutations caused impaired neurogenesis in cerebral organoids (Inak et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…Mutations in various genes involved in mitochondrial respiration have been described. These genetic dysregulations have been associated with severe neurodevelopmental disorders ( Baertling et al, 2014 ; Inak et al, 2019 ; Lake et al, 2016 ; Romero-Morales et al, 2020 ; Winanto et al, 2020 ). The reduction of oxygen by the electron transport chain leads to reactive oxygen species (ROS) superoxide byproducts, the accumulation of which can be damaging to cellular processes.…”
Section: An Overview Of the Development Of The Human Cortexmentioning
confidence: 99%
“…Disproportionate levels of either mitochondrial fusion or fission results in profound pathological abnormalities, as well as neurodegenerative diseases such as Charcot-Marie-Tooth syndrome and dominant optic atrophy caused by mutations in MFN2 and OPA1 , respectively ( Züchner et al, 2004 ; Alavi et al, 2007 ; Davies et al, 2007 ; Waterham et al, 2007 ). Although the majority of individuals with OPA1-related diseases have symptomatic optic neuropathy, other rare associations with spastic paraplegia ( Carelli et al, 2015 ; Verny et al, 2008 ; Yu-Wai-Man et al, 2010 ), and syndromic parkinsonism and dementia ( Carelli et al, 2015 ), reported severe defects in early neurogenesis due to depletion of neural progenitor cells or cortical specification ( Inak et al, 2019 ; Romero-Morales et al, 2020 ) suggest that OPA1 function is essential in many areas of the central nervous system, particularly the cortex.…”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%